Strategic Decision Making in Construction Supply Chains: A Comparison of Reverse Logistics Strategies - Pushpamali, NNC; Agdas, Duzgun; Rose, Timothy M. (Frontiers in Built Environment, 2020)
Most of the construction materials still go to landfill after structures are demolished. This causes issues in human health, ecosystem preservation, and excessive resource consumption compared to RL options. Hence, recovering material value through reverse logistics (RL) is important to lessen the environmental and social burden. Embodying RL practices into strategic level decisions derives long-term and sustainable advantages. Although the most common RL option in construction seems to be recycling, it requires an additional energy and material intensive process. Therefore, recycling should be the last preference among other RL options. The hypothesis of this study is that alternative RL strategies provide more environmental benefits than recycling, the most common RL method, and traditional landfilling. The hypothesis was tested through assessment of the environmental impact of RL options in the construction sector. A life cycle assessment (LCA) with ReCipe2016 Midpoint and Endpoint assessment method was conducted for a bridge construction supply chain. Different end-of-life scenarios such as reuse, remanufacture, recycle, and landfill scenarios were assessed using SimaPro software. This paper addresses a key knowledge gap on the environmental impact of reverse logistics strategies from a construction supply chain perspective. The research results reveal that ‘reuse’ strategy has the least environmental impact, remanufacturing has a lesser impact on the environment than other options, recycling has the second highest environmental impact, with landfill assessed as the least environmentally friendly end-of-life option. Consequently, this paper emphasises the importance of informed strategic supply chain decisions for reverse logistics to obtain the best outcome from environmentally friendly practices. Since there is no relevant previous research conducted to examine the environmental impact of different reverse logistics options from a construction supply chain perspective, the findings of this study provide crucial input in RL decision making and can extend to contributing to practice. Industry stakeholders, especially the government agencies and regulatory bodies, should encourage practitioners to adopt the most effective RL approaches, including reuse and remanufacturing, rather than focusing only on material recycling. The motivation of supportive designs for more environmentally friendly RL options from the researchers, designers, architects, and planners are required in this process.